Peran Kota Kecil Dalam Perkembangan Wilayah Pada Koridor Jalan Regional Semarang - Yogyakarta - Hidayati, Solikhah Retno (Magister Pembangunan Wilayah dan Kota,Undip, 2015)
The small towns development are becoming an important issue in regional development. They should be able to hold their role as a service center for their upper region and hinterland. It is no exception in Joglosemar corridor.Yogyakarta, Solo, and Semarang, has now been developing as economic center in Java. The role of small towns among them has been decreased because of the big city primacy. This study aim to identify how the small towns hold their role in Semarang-Yogyakarta corridor. The role are viewed from spatial and economic aspect. The indicator of spatial aspect are urban primacy (Zipf’s rank-size rule), polarization (population growth), and service center (centrality index). The economic indicators are regional disparity (Williamson index), economic base (LQ), and economic performance (shift and share). The regional area will be studied from two point of view, they are micro (among small towns and to the hinterland) and macro (to the kabupaten and province).